The relationship between ethical climate organisational commitments and ethical behaviour in a distribution and warehoursing organisation - Zondi, Zama (School of Management Studies, 2025)
This study examined the relationship between ethical climate, organisational commitment, and ethical behaviour within a warehousing and distribution organisation, Laser Logistics. It aimed to understand how these variables relate to and predict each other within a specific organisational context. A quantitative approach was adopted, and data were collected from a convenience sample of 86 participants across different management levels via a structured online questionnaire, combining validated measures. Descriptive statistics, Pearson's correlation, and simple linear regression analyses were used to analyse the data. Results indicated a moderate, statistically significant positive correlation between organisational commitment and ethical climate, suggesting that a supportive ethical environment may enhance employee commitment to the organisation. However, the relationships between organisational commitment and workplace behaviour, and between ethical climate and workplace behaviour, were found to be weak and statistically non-significant. The study contributes to the broader understanding of these dynamics and recommends future research to explore further variables that may affect workplace behaviour in a similar organisational setting.